Recontextualizing Ki Hajar Dewantara’s Educational Philosophy in the Era of Merdeka Belajar and Global Disruption - Ismaiza Busti; Refinal; Saifullah SA; Desi Asmaret; Julhadi; Usman Aliyu Yunusa (Walidem Institute and Publishing, 2026)
Objective: To critically analyze Ki Hajar Dewantara's educational philosophy and its relevance to contemporary Indonesian education, especially in the context of the